Increased Transmissibility of Leishmania donovani From the Mammalian Host to Vector Sand Flies After Multiple Exposures to Sand Fly Bites. (9th March 2017) - Valverde, Joanna G.; Paun, Andrea; Inbar, Ehud; Romano, Audrey; Lewis, Michael; Ghosh, Kashinath; Sacks, David
Abstract: Background: Patients with active visceral leishmaniasis are important reservoirs in the anthroponotic transmission cycle of Leishmania donovani . The role of the blood or skin as a source of infection to sand flies remains unclear, and the possible effect of multiple exposures to fly bites on transmissibility has not been addressed. Methods: L. donovani –infected hamsters underwent xenodiagnoses with Lutzomyia longipalpis on the same or different sites on the abdomen on 2 consecutive days or by artificial feeding on the skin or blood. Results: The transmission of L. donovani from sick hamsters to flies was surprisingly low (mean, 24% of fed flies). New flies fed on the same site acquired significantly more infections (mean, 61%; P < .0001). By artificial feeding, flies could acquire infection from blood and skin. However, only artificial feeding on blood produced infections that correlated with the natural feeding (R = 0.792; P < .0001). Infections acquired from blood increased dramatically for blood obtained after exposure to bites, as did the parasitemia level and the number of monocytes in the circulation. Conclusions: The bites of uninfected sand flies favor the transmissibility of L. donovani by infected hosts, owing to a systemic effect that exposure to bites has on the parasitemia. Patients with active visceral leishmaniasis are important reservoirs in the anthroponotic transmission cycle of Leishmania donovani. Using the hamster model of visceral disease, we demonstrate that prior exposure to bites of uninfected sand flies potentiates their ability to transmit infection to the vector.